PENGGUNAAN ISTILAH TEKNIS DALAM NOVEL SERIAL SUPERNOVA KARYA DEWI LESTARI - Rasyid, Sabhan; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Supernova serial novel is a phenomenal novel by Dewi Lestari which began publishing for its first title in 2001. The first novel is called Ksatria, Putri, dan Bintang Jatuh. This novel has also been successfully filmed on the big screen of this country. After that, Dewi Lestari continued the series from this Supernova until the sixth title. The titles of the novel Akar (2002), Petir (2004), Partikel (2012), Gelombang (2014), dan yang terakhir Intelegensi Embun Pagi (2016). Researchers on this occasion examined the entire title of the novel Supernova. The analysis will be done, namely by looking at the use of technical terms in the novel. The details of this research problem, namely to analyze the meaning of lexical, grammatical meanings, and contextual meaning of the technical terms that exist in the novel Supernova. Researcher use descriptive research method with qualitative approach. The data and data sources from this research is a technical term that exists in the six novels Supernova. This research is related to learning material in high school class X in the material of learning novel of Curriculum 2013. This research yields several conclusions, namely 1) technical terms inventoried and analyzed can be classified into many fields of science and study groups, such as Biology, Chemistry, Physics, Mathematics, Sociology, Anthropology, Greek Mythology, Theology, Computers and Internet, Astronomy, Space, and Psychology. 2) The process of analyzing the lexical meaning of technical terms in the six novels Supernova done by looking at the meaning of KBBI, Dictionary of Terms, Encyclopedia of Science, Journal of Science, and Book of Religious. 3) The process of analysis of the grammatical meaning of technical terms in the six novels Supernova done by looking at the composition of the sentence and the author's intention in conveying the message of the story. 4) The process of analyzing the contextual meaning of technical terms in the six novels Supernova done by looking at the background of the author, background story, and sociological and psychological conditions of society when the novel was written. 5) A total of 266 technical terms are analyzed based on lexical meanings, grammatical meanings, and contextual meanings in all six Supernova novels that can be used as documents to make it easier to understand the novel story of Supernova.Â Keyword: Supernova, technical terms, lexical, grammatical, contextual